2020
DOI: 10.3389/fphar.2020.529654
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Pharmacist–Physician Collaborative Management for Patients With Idiopathic Pulmonary Fibrosis Receiving Pirfenidone

Abstract: Background: Pirfenidone is an anti-fibrotic agent used to treat patients with idiopathic pulmonary fibrosis (IPF). Managing adverse drug events and ensuring compliance with pirfenidone treatment for a prolonged period are important to reduce the rate of disease progression. To maximize the benefits of pirfenidone treatment, we established and evaluated an ambulatory care pharmacy practice, a model of pharmacist–physician collaborative management, for patients receiving pirfenidone.Methods: We conducted a retro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…Four studies reported better medication adherence (three medication support programmes [ 39 , 77 , 89 ]; one home monitoring programme [ 40 ]). One palliative care programme reported increased use of antifibrotic therapy [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…Four studies reported better medication adherence (three medication support programmes [ 39 , 77 , 89 ]; one home monitoring programme [ 40 ]). One palliative care programme reported increased use of antifibrotic therapy [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…The value of pharmacist-led team care in pharmacotherapies has been demonstrated in numerous studies ( Yamamoto et al, 2018 ; Escudero-Vilaplana et al, 2020 ; Satsuma et al, 2020 ; Ji et al, 2021 ; Jia et al, 2021 ; Marzal-Alfaro et al, 2021 ; Miura et al, 2021 ; Xu et al, 2021 ). The results of this study revealed that pharmacist-urologist collaborative management can also improve care for patients with CRPC receiving enzalutamide in an ambulatory care setting.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that patient-centered, multidisciplinary team care, which provides support, information, and empowerment to cancer patients receiving chemotherapy, is effective ( Pillay et al, 2016 ; Lutfiyya et al, 2019 ; Xie et al, 2021 ). In addition, we developed a pharmacist-physician collaborative management system for patients with idiopathic pulmonary fibrosis receiving pirfenidone treatment, and reported the efficacy of this approach ( Satsuma et al, 2020 ). Based on these, in October 2016, we developed an ambulatory care pharmacy practice that allows pharmacist–urologist collaboration for the management of patients with CRPC receiving ASIs, including enzalutamide.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, a well-coordinated effort between doctors, nurses, and pharmacists can prevent medication errors, optimize therapeutic regimens, and ensure holistic patient care [ 6 , 7 ]. Hospital pharmacists are vital contributors to healthcare systems, working with doctors, nurses, and allied health professionals in diverse settings—from inpatient bedsides to emergency departments and outpatient clinics [ 8 ].…”
Section: Introductionmentioning
confidence: 99%